« Paysages avec figures absentes » : La peinture d’Elsa Maldiney - Éliane Escoubas (Projets de Paysage)
Elsa Maldiney's painting offers several stages. One of them, among the first ones, up until 1960 without a doubt, is probably the one of painting landscapes – but landscapes which are not landscape-shows but landscape-milieus engendered by the march of an invisible walker. The last stage, from the last decade of the 20th century and since 2000, is the one of a purely abstract painting, of a coloured energy, of outbursts, ruptures, and meetings – in a word: the one of a field of tensions, which is rhythm.